Proximal and distal intragastric meal distribution during gastric emptying scintigraphy: Relationships to symptoms of gastroparesis. Issue 12 (5th August 2022) - Silver, Paul J.; Dadparvar, Simindokht; Maurer, Alan H.; Parkman, Henry P.
Abstract: Background: Total gastric retention (TGR) from gastric emptying scintigraphy (GES) is used for diagnosing gastroparesis (Gp), but correlates poorly with patients' symptoms. Regional intragastric meal distribution (RIMD) can also be assessed from GES. This study classified patients' meal distribution as proximal or distal to relate RIMD to symptoms of Gp. Methods: GES studies in patients ( n = 193) and control subjects ( n = 21) were selected for RIMD analysis. Patients completed Patient Assessment of Upper Gastrointestinal Symptoms (PAGI‐SYM) for symptom severity before GES. TGR was analyzed using % TGR, and RIMD used a proximal/distal gastric count ratio (PDCR). Results were classified as proximal or distal RIMD at 0, 1, 2, and 4 h postprandially based on their PDCR being above or below the median value of the patients. Results: Patients with delayed GE and immediate post‐meal ingestion distal distribution had more severe early satiety and regurgitation. Distal distribution at 1 h had more severe early satiety and loss of appetite compared to proximal distribution. Patients with delayed GE and proximal distribution at 4 h had more severe nausea, retching, and vomiting compared to 4 h distal distribution. Severely delayed 4 h proximal distribution had more nausea than severely delayed 4 h distal distribution. Conclusions: Increased early distal IMD in patients with delayed GE was associated with regurgitation and early satiety whereas increased late proximal IMD was associated with nausea, retching, and vomiting. Differentiating proximal from distal meal distribution patterns helps to relate symptoms to gastric dysfunction and may be helpful for directing therapy. Abstract : Early distal intragastric meal distribution was associated with regurgitation, early satiety, and postprandial fullness whereas late proximal distribution was associated with nausea, retching, and vomiting. Differentiating proximal from distal gastric distribution helps to relate symptoms to gastric dysfunction and may be helpful for directing therapy.